Notes on Polychaeta from the coast of western Canada. III. Further notes on Syllidae and some observations on other Polychaeta errantia - Berkeley, E.; Berkeley, C. (Annals and Magazine of Natural History, 12 (Series, 1945)
Introduction: "In Part II. of this series (Berkeley, E. & C., 1938, p. 33) we recorded thirteen species of Syllidae new to the coast of western Canada, and made some comments on .species belonging to that family which had been recorded there previously. Recent work makes it necessary to add another species, which we believe to be undescribed, to the family, and to make some further comments on others. During the last few years we have revised our collections from this coast and some newly collected material has been examined. The work has brought to light some new species and several new records in many of the families other than Syllidae, and has indicated that modifications and amendments are necessary in cases of species previously recorded. The greater part of the present paper consists of these records and amendments. The types of the new species are in the authors' collection,
Polychaeta DB